(untitled) (Homoeopathy for All, 2022)
Sciatic nerve is the largest nerve in the body which originates from the sacral plexus, formed by the roots (anterior rami) of spinal nerves L4– L5 and S1–S4. Sciatica is a type of Lumbar Radicular Pain (LRP)1 and is the most common form of back pain, caused by compression or irritation of the sciatic nerve. The typical presentation of sciatica is a pain that extends from the buttock down the posterior and lateral aspect of the leg and the lateral aspect of the foot.